(untitled) (Fiep Bulletin - online, 2013)
Violence is a problem that produces threat to life, physical integrity, life quality, and is the precursor of several injuries and trauma, constituting a major public health problem, not restricted only in this sector, but the whole society. In this sense, it is essential to look at the trends of scientific literature addressing the impact of violence on the occurrence of injuries and trauma in their victims. This is a literature research, whose purpose is to analyze the scientific production of Latin America and the Caribbean, involving violence, injury and trauma, published in the period from 2004 to August 2008 in the databases of Literature Latin American and Caribbean Health Sciences (LILACS), indexed in the Virtual Health Library / Regional Library of Medicine (BVS/BIREME). It was found 18 works, which, after refinement, were selected. Of this total (18), 06 (33.3%) were published in 2006; 14 (77.8%) used the descriptive study type, 12 (66.7%) of the publications had approached the quantitative method as the best way to notify the injuries and trauma resulting from violence; 13 (72.2%) were more available in full-text form, 9 (50.0%) were available in Spanish language; as a factor causing the injuries and trauma stood out the violence that occurred in traffic (27.8%), and Brazil (50.0%) was the country that most published over the past 5 years. It follows that the priority is to continue to carry out research on those topics and, at the same time, investing in the development of researches directed to the clinical severity of injuries caused by violence, contributing to a better preparation of health professionals who work in the healthcare assistance of these victims.